All-trans-retinoic-acid and arsenic trioxide induced remission in promyelocytic blast crisis. (2018) - Colvin, Teresa A.; Vachhani, Pankit; Sait, Sheila; Neppalli, Vishala; Wang, Eunice S.
Abstract: A 78-year-old-male with chronic myeloid leukemia (CML) treated for seven years with dasatinib developed an acute promyelocytic leukemia complicated by disseminated intravascular coagulopathy. A promyelocytic blast crisis was diagnosed by demonstrating co-expression of chimeric BCL/ABL and PML/RARα translocations by karyotyping, fluorescence in situ hybridization, and quantitative real-time polymerase chain reaction. Promyelocytic blast crisis of CML is a rare event with historically poor outcomes. Treatment of our patient with all- trans -retinoic acid (ATRA) and arsenic trioxide (ATO) resulted in complete morphologic remission. We review here the relevant literature of promyelocytic blast crisis and highlight the potential of ATRA/ATO as first line management.